Accumulation and Archives: Sophie Calle’s Prenez soin de vous - Natalie Edwards (Studies in 20th & 21st Century Literature, 2014)
French project artist Sophie Calle has become well-known for her iconoclastic performance art that blends visual and textual elements. Beginning with Les Dormeurs in 1979, in which she invited 24 strangers to sleep in her empty bed and photographed them hourly, through her project of following people around Paris and photographing them like a private detective in Suite vénitienne, Calle has blurred the boundaries between private and public, between photographer and photographed, and between viewer and participant. In this article, I focus on her recent exhibition, Prenez soin de vous. The title comes from the last line of an email received by Calle in which a lover ends their relationship. Rather than answer, file, or simply delete the message, Calle gave a copy of it to 107 women and asked them each to respond to it from the perspective of their different professions. Thus a singer sings it, a philosopher writes a piece in response to it, a DJ raps it, an accountant talks about the financial implications of it, a sexologist analyzes it, a typesetter corrects it and so on. The result is a mixed-media exhibit consisting of texts, photographs, films, and recordings. Although this was originally staged for the Venice Biennale of 2007, this paper looks specifically at the way in which it was staged in France: in the former Bibliothèque Nationale de France, rue Richelieu. In this article, I analyze this exhibit in terms of the accumulation that it stages. I show that the exhibit performs a hoarding of objects from different sources that, taken together, takes the notion of collective autobiography into new terrain. Through a discussion of Derrida’s Mal d’archive, I examine the living archive that the exhibition comprises. Interpreted in terms of the Bibliothèque Nationale that housed them, the textual and visual artifacts of this exhibition become an accumulation within a site of accumulation and push Calle’s innovation further, beyond the re-inscription of female subjectivity, the play between seeing and being seen, and the blurring of the public and private for which she is already celebrated.
Keywords: Sophie Calle; archive; accumulation; exhibition; Derrida; selfhood